2014
DOI: 10.1016/j.socscimed.2013.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Social capital, mental health and biomarkers in Chile: Assessing the effects of social capital in a middle-income country

Abstract: In high-income countries, higher social capital is associated with better health. However, there is little evidence of this association in low- and middle-income countries. We examine the association between social capital (social support and trust) and both self-rated and biologically assessed health outcomes in Chile, a middle-income country that experienced a major political transformation and welfare state expansion in the last two decades. Based on data from the Chilean National Health Survey (2009–10), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 62 publications
7
42
0
Order By: Relevance
“…It was not possible to control for this problem by, for example the inclusion of instrumental variables because of the absence of suitable candidates for instrumental variable analysis in the small questionnaire. However, although the potential for a bidirectional relation exists, among the 12 longitudinal studies on the effect of social capital on mental health that we identified, nine studies demonstrated that social networks are protective against mental ill health [ 24 , 43 50 ] with only three studies showing mixed results [ 45 , 51 , 52 ]. Residual confounding is also a potential problem in this study, as we could not adjust for variables such as war-related experiences, previous clinical history, alcohol or other drug use and unemployment which are all risk factors for mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It was not possible to control for this problem by, for example the inclusion of instrumental variables because of the absence of suitable candidates for instrumental variable analysis in the small questionnaire. However, although the potential for a bidirectional relation exists, among the 12 longitudinal studies on the effect of social capital on mental health that we identified, nine studies demonstrated that social networks are protective against mental ill health [ 24 , 43 50 ] with only three studies showing mixed results [ 45 , 51 , 52 ]. Residual confounding is also a potential problem in this study, as we could not adjust for variables such as war-related experiences, previous clinical history, alcohol or other drug use and unemployment which are all risk factors for mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, most studies are from Occident in 17 included articles, while in LMIC these kinds of studies are rare (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), so the effect of social capital on NCDs in these countries is not known. Social capital was measured by individual cognition and behavior, and the ecological data were aggregated from the individual level, and there is no effective method to measure social capital precisely and directly at present.…”
Section: Discussionmentioning
confidence: 99%
“…It has three different types of network resources including bonding social capital to bring people/groups who already know each other together; bridging social capital to bring people/groups who previously did not know each other and are outside each other's group together through interactions during any common tasks within a community; linking social capital to bring people/groups together from "different social strata in a hierarchy where power, social status, and wealth are accessed by different groups" [3]. Social capital has been demonstrated to be a determinant of many aspects of health, such as physical health, mental health, emotional health and social health, among different populations across the lifespan [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. It improves individuals/communities' access to health relevant information; provides individuals/communities with informal healthcare and support in case of illness; and improves the effectiveness of health advocacy through well-organized and connected groups [1].…”
Section: Introductionmentioning
confidence: 99%
“…Whether it is at an individual or an aggregated level, the linkage between social capital and incidence and prevalence of morbidity/mortality of different health outcomes has been consistently proven true among many other populations in many other countries (e.g., Finland, China, U.S.) [9][10][11]. Literature further emphasized the significance of the impact of social capital on mental health [12][13][14][15][16][17][18][19][20][21]. A total of 2,624 adult residents from 300 census tracks in Canada, who was part of the 2008 Montreal Neighbourhood Networks and Healthy Ageing Study were surveyed.…”
Section: Introductionmentioning
confidence: 99%